A Case Study of Orange Juice Concentration by Recompression Evaporation Techniques. Issue 3 (22nd August 2012) - Sorour, M.A.; Mostafa, S.R.; Bo Samri, S.M.
Abstract Evaporation is commonly used by various processing industries as a method of concentrating aqueous liquid streams by vaporizing the water component. The comparison of two schemes of evaporation was studied and economically analyzed. Recompression evaporation could be defined as an evaporation process in which a part or the entire evaporated vapor is compressed by means of a suitable compressor to a higher pressure level and then condensed. Two recompression schemes were studied: (1) mechanical compression; and (2) thermal compression. Different economic items, including cost of steam, electricity, fixed cost of compressor and cost of evaporator, in addition to annual total cost for each scheme have been estimated and analyzed. The results indicated that minimum annual total cost is obtained by using a steam jet ejector scheme. Practical Applications It is essential that evaporation be approached from the viewpoint of economical energy utilization as well as process effectiveness. This can be done only if the equipment manufacturer is able to offer a full selection of evaporation technology and systems developed to accommodate various product characteristics, the percent of concentration required and regional energy costs.